2014
DOI: 10.1111/dom.12412
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐lowering with exogenous insulin monotherapy in type 2 diabetes: dose association with all‐cause mortality, cardiovascular events and cancer

Abstract: There was an association between increasing exogenous insulin dose and increased risk of all-cause mortality, MACE and cancer in people with type 2 diabetes. The limitations of observational studies mean that this should be further investigated using an interventional study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 43 publications
2
54
0
3
Order By: Relevance
“…Our study, similarly to observations by Currie et al [10] and Li et al [24] revealed elevated risk of malignancy associated with insulin use, but only when not combined with metformin. This relationship was dose-dependent, which was also found by Holden et al [25]. Metaanalysis by Janghorbani et al demonstrated increased risk of malignancy associated with insulin use after 4 years of insulin treatment [23].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our study, similarly to observations by Currie et al [10] and Li et al [24] revealed elevated risk of malignancy associated with insulin use, but only when not combined with metformin. This relationship was dose-dependent, which was also found by Holden et al [25]. Metaanalysis by Janghorbani et al demonstrated increased risk of malignancy associated with insulin use after 4 years of insulin treatment [23].…”
Section: Discussionsupporting
confidence: 63%
“…These observations can be explained by relatively short duration of these studies, frequent metformin use in combination with insulin, and, in addition, relatively low doses of insulin used in the ORIGIN trial. It should also be noted that the risk of malignancy associated with insulin use does not depend neither on the type of insulin (human or analog) [9,33,34], nor on the insulin treatment regimen (basal, basal/bolus or premixed) [25].…”
Section: Discussionmentioning
confidence: 99%
“…As a previous report suggested, reduction of the pancreatic β cell load could result in improved pancreatic β cell function by Ipra [14]. Further, it was recently reported that too much insulin injection and consequent hyperinsulinemia might be a risk of cardiovascular events and cancer [15]. Reduction of S-CPR and serum insulin concentration could be beneficial not only for pancreatic β cell protection but also for preventing cardiovascular events and cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Нарастает количество данных, свидетельствующих о негативном влиянии инсулина на сердечно-сосудистый и онкологический риск при СД2 [18,19]. Интересно от-метить, что результаты последних исследований еще раз окончательно подтвердили влияние пиоглитазона на раз-витие рака мочевого пузыря [20,21].…”
Section: E (Energy) энергетическая (гравицентрическая) кон-цепция теunclassified